P-004 Retreatment and Rebleed Rates of Coiled Aneurysms with Respect to the Raymond-Roy Scale, a Meta Analysis. (14th July 2013) - Darflinger, R; Urdaneta, A; Chao, K; Feng, L
Abstract : Introduction: We tend to use the Raymond-Roy scale for aneurysm occlusion although its significance in terms of long term durability and outcome has not been established. Although there is a tendency of higher recurrence after initial aneurysm coiling with higher grades, the retreatment rates and rebleed rates are less understood. We conducted a meta-analysis to study the retreatment and rebleed rates after initial aneurysm coiling. Method: We performed a meta-analysis utilising publications in pubmed for cerebral aneurysm coiling retreatment and rebleed. We then analysed papers with data that provided initial aneurysm coiling results using the Raymond-Roy system or some variation. We selected data with at least 1 year follow up. Given staged treatment, we defined retreatment as occurring greater than 3 month to exclude intentionally incomplete treatment. Rebleed was defined as greater than 1 month to exclude periprocedural complications. Results: Initial angiographic results after aneurysm coiling utilising Raymond-Roy scale: grade 1 - 53%, grade 2 - 34%, grade 3 - 13%. For those aneurysms with initial grade 1 occlusion, there was 11% recurrence, 5% retreatment, and <1% rebleed. For those aneurysms with initial grade 2 neck remnant, there was 16% recurrence, 4% retreatment, and <1% rebleed. For those aneurysm with initial grade 3 residual aneurysm, there was 18% recurrence, 11% retreatment, and <1% rebleed. Although there was a difference in aneurysm recurrence after initial treatment, grade 1 and 2 demonstrated no significant difference in retreatment and rebleed. Conclusion: The Raymond-Roy scale provides predictive value for recurrence but less predictive value for retreatment and rebleed of cerebral aneurysms after coiling. Furthermore, grade 1 and 2 coiled aneurysms may not have any impact on clinical outcome given similar rates of retreatment and rebleed. Disclosures: R. Darflinger: None. A. Urdaneta: None. K. Chao: None. L. Feng: None.